Measurement of Attitude of Rural Families with Handicapped Member(s) towards Handicappeds in Fields Where Community Based Rehabilitation (C.B.R.) Has Excuted with Those who Has Not - Behzad Sattari; Khosrow Omidvar; Vali Ya'ghoubi (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: The present research has been done to study the affectability of executing the community based rehabilitation plan due to the way rural families with one or more handicapped members view to the handicapped and disability. Some other parameters such as the level of education, city of dwelling, presence or absence of community based rehabilitation plan execution, job, age, sex, and being acquainted with welfare have been considered in this regard. Materials & Methods: The statistical community of the research include all rural families in Ardebil province in 2004. Using the "random multi - step sampling" method, 173 families and 346 people (two for each family) participated in the task. The research equipment was the researcher made questionnaire in which 31 questions on the basis of Likert scale, in addition to the demographic section, had been designed to measure the attitude of families, in this research "survey cross - section" approach has been used. Using the SPSS software, extracted data were analyzed, and in in formation describing section, the average score of the attitude towards the handicapped, variance of the scores, standard deviation of the scores, etc., and in the section for analyzing and reasoning, the one - way variance analyzing method (ANOVA), Scheffe Post Hoc, and regarding the two independent groups T testing have been used. Results: from the research showed that in comparison with other areas, in areas where the community based rehabilitation plan has been executed, there is a more appropriate attitude towards the disability phenomenon. Also, some other variables such as the level of education, sex, being acquainted with welfare have been effective on viewing to wards the handicapped. Other variables showed no significant differences concerning the attitudes to wards the handicapped. Conclusion: In areas where the community based rehabilitation plan has been executed, there is a more appropriate attitude towards the disability phenomenon.